Motion Estimation in Medical Imaging - S., Ranjit; K. S., Sim; R., Besar; C. P., Tso (SPRINGER, 2008)
This paper presents a study on Magnetic Resonance Imaging (MRI) by using the hexagon-diamond search (HDS) method. The HDS algorithm is implemented on the MRI images in order to obtain statistically relevant results. The HDS algorithm extracts images into macro-blocks and performs the computation for image redundancy between frames. In addition, HDS algorithm also preserves the global properties of images while maintaining the performance. With the implementation of HDS algorithm, the processing time can be reduced and the complexity of computation is also reduced.